2011
DOI: 10.1111/j.1745-4530.2010.00615.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Simplified Numerical Model for Hot‐air Treatment of Egg Shell Surface

Abstract: The aim of the study was to simulate a hot‐air‐based treatment of the egg shell by a simplified finite element model. The calculated temperatures were compared with experimental data observed on an egg shell instrumented with thermocouples. A simple plant was used to make eggs roll while hot and cold air jets impinged the shell on opposite sides. The results have shown good agreement between calculated and observed temperatures on the inner part of the shell, despite the simplicity of the 2D numerical model. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Moreover to validate the CFD model an egg simulant was set up. Tests conducted at different combinations of air flow rate and treatment duration compared with simulated results obtained a correlation index higher than 91% (Fabbri et al, 2009). …”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Moreover to validate the CFD model an egg simulant was set up. Tests conducted at different combinations of air flow rate and treatment duration compared with simulated results obtained a correlation index higher than 91% (Fabbri et al, 2009). …”
Section: Resultsmentioning
confidence: 87%
“…The detail of the model development and validation are described by Fabbri, Cevoli, and Giunchi (2009).…”
Section: Hot Air Treatment Technique and Modellingmentioning
confidence: 99%
“…A prototype for hot air treatment was built based on results obtained by a numerical model of thermal interactions between the air, the shell, and the internal egg content (Fabbri et al 2009). The best thermal treatment was selected for the highest decontamination efficacy without any negative effects on egg quality.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that air cells have heat resistant characteristics (Fabbri et al. ). However, to our knowledge, no previous researchers have developed a general model for eggs pasteurization considering all parts of an egg such as white, yolk, and air cell.…”
Section: Introductionmentioning
confidence: 99%